ANALISIS PENERAPAN PSAK 109 MENGENAI AKUNTANSI ZAKAT DAN INFAQ/SEDEKAH PADA BAITUL MAL ACEH - Murniati Murniati; Adhisyahfitri Evalina Ikhsan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This research aims to analyze the implementation of PSAK 109 in Baitul Mal Aceh. This research was conducted to look how PSAK 109 was applied in Baitul Mal Aceh. This research uses questionare as the primary data and financial statement as the secondary data. The subject of this research is Baitul Mal Aceh and the object is financial statement of 2016 period. This research is a descriptive research, data analysis in this study uses descriptive-comaparative analysis. The result of this study shows that there are four indicators of PSAK 109. Baitul Mal Aceh has applied 94% of PSAK 109.